Efficacy and safety of Panax notoginseng saponins (Xuesaitong) for patients with acute ischemic stroke: a systematic review and meta-analysis of randomized controlled trials - Shi, Xinyi; Feng, Luda; Li, Yixuan; Qin, Mingzhen; Li, Tingting; Cheng, Zixin; Zhang, Xuebin; Zhou, Congren; Cheng, Sisong; Zhang, Chi; Gao, Ying (Frontiers in Pharmacology, 2023)
Background: Stroke is the major cause of mortality and permanent disability and is associated with an astonishing economic burden worldwide. In the past few decades, accumulated evidence has indicated that Xuesaitong (XST) has therapeutic benefits in cases of acute ischemic stroke (AIS). Our study aimed to provide the best current body of evidence of the efficacy and safety of XST for patients with AIS.Methods: This is a systematic review and meta-analysis of randomized controlled trials. We searched 8 electronic databases from inception to July 17, 2023, for relevant randomized controlled trials. The investigators independently screened trials, extracted data, and assessed the risk of bias. A metaanalysis was conducted using RevMan 5.3 and STATA 16.0 software.Results: Forty-six randomized controlled trials involving 7957 patients were included. The results showed that XST improved the long-term functional outcomes with lower mRS scores (MD = -0.67; 95% CI [-0.92 to -0.42]; p < 0.00001) and a higher proportion of functional independence (mRS ≤ 2) (RR = 1.08; 95% CI [1.05 to 1.12]; p < 0.00001). Low-quality evidence indicated that XST improved the activities of daily living (MD = 10.17; 95% CI [7.28 to 13.06]; p < 0.00001), improved the neurological impairment (MD = -3.39; 95% CI [-3.94 to -2.84]; p < 0.00001), and enhanced the total efficiency rate (RR = 1.19; 95% CI [1.15 to 1.23]; p < 0.00001). No significant difference was found in the all-cause mortality or incidence of adverse events between the XST and control groups. The certainty of evidence was estimated as moderate to very low. Conclusion: Presently, the administration of XST within 14 days for AIS is associated with favorable long-term functional outcomes. Besides, XST can improve activities of daily living and alleviate neurological deficits, and has shown its good tolerability. However, the current evidence is too weak and the confidence of evidence synthesis was restricted by the high risk of bias. Given the insufficient evidence, appropriately sized and powered RCTs investigating the efficacy and safety of XST for patients with AIS are warranted.